HUBUNGAN PEMBERIAN ASI EKSLUSIF, ASUPAN MAKRO, ASUPAN MIKRO DAN PENYAKIT INFEKSI PADA BALITA DENGAN KEJADIAN STUNTING DI WILAYAH KERJA PUSKESMAS ANAK AIR TAHUN 2021 - Rahmita Yanti (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Stunting is a nutritional status that indicates a lack of intake, chronic and recurrent infectious diseases and is characterized by TB/U below (<-2SD) standard deviation according to the World Health Organization (WHO) 2005. The results of the survey on stunting in children under five, the Padang City Health Office in 2018 and 2019 it is known that the highest prevalence of stunting at the Air Children's Health Center was around 33.33% to 23.51%. This study aims to determine the relationship between exclusive breastfeeding, macro intake, micro intake, and infectious diseases in toddlers with the incidence of stunting in the work area of the Water Children Health Center in 2021.This type of research is an analytic survey with a cross sectional approach. The research was conducted in the working area of the Anak Air Health Center which was held in June-July 2021 with a total sample of 77 respondents. Sampling was done by Simple Random Sampling. The dependent variable of the study was the incidence of stunting with a microtoise/stature meter, while the independent variables were exclusive breastfeeding using a questionnaire, energy intake, protein intake, zinc intake, iron intake using the SQ-FFQ form and infectious diseases using a questionnaire. Data analysis using Chi-Square test on SPSS version 26 program.The results showed that there was a significant relationship between exclusive breastfeeding (p= 0.004), energy intake (p= 0.000), protein intake (p= 0.003), zinc intake (p= 0.013), iron intake (p= 0.011). and infectious diseases (p= 0.029) with stunting in children under five in the Padang City Water Health Center in 2021.The research suggests the active role of the government, especially health workers, to tackle stunting in children under five. In addition, it is hoped that parents can pay attention to their child's nutritional intake so that the child's nutritional adequacy is fulfilled and can prevent stunting.